Vascular Expression of Hemoglobin Alpha in Antarctic Icefish Supports Iron Limitation as Novel Evolutionary Driver - Corliss, Bruce A.; Delalio, Leon J.; Stevenson Keller, T. C.; Keller, Alexander S.; Keller, Douglas A.; Corliss, Bruce H.; Beers, Jody M.; Peirce, Shayn M.; Isakson, Brant E. (Frontiers in Physiology, 2019)
Frigid temperatures of the Southern Ocean are known to be an evolutionary driver in Antarctic fish. For example, many fish have reduced red blood cell (RBC) concentration to minimize vascular resistance. Via the oxygen-carrying protein hemoglobin, RBCs contain the vast majority of the body's iron, which is known to be a limiting nutrient in marine ecosystems. Since lower RBC levels also lead to reduced iron requirements, we hypothesized that low iron availability was an additional evolutionary driver of Antarctic fish speciation. Antarctic Icefish of the family Channichthyidae are known to have extreme alteration of iron metabolism due to loss of two iron-binding proteins, hemoglobin and myoglobin, and no RBCs. Loss of hemoglobin is considered a maladaptive trait allowed by relaxation of predator selection, since extreme adaptations are required to compensate for the loss of oxygen-carrying capacity. However, iron dependency minimization may have driven hemoglobin loss instead of a random evolutionary event. Given the variety of functions that hemoglobin serves in the endothelium, we suspected the protein corresponding to the 3’ truncated Hbα fragment (Hbα-3’f) that was not genetically excluded by icefish, may still be expressed as a protein. Using whole mount confocal microscopy, we show that Hbα-3’f is expressed in the vascular endothelium of icefish retina, suggesting this Hbα fragment may still serve an important role in the endothelium. These observations support a novel hypothesis that iron minimization could have influenced icefish speciation with the loss of the iron-binding portion of Hbα in Hbα-3’f, as well as hemoglobin β and myoglobin.